2003
DOI: 10.1083/jcb.200212085
|View full text |Cite
|
Sign up to set email alerts
|

Back signaling by the Nrg-1 intracellular domain

Abstract: Transmembrane isoforms of neuregulin-1 (Nrg-1), ligands for erbB receptors, include an extracellular domain with an EGF-like sequence and a highly conserved intracellular domain (ICD) of unknown function. In this paper, we demonstrate that transmembrane isoforms of Nrg-1 are bidirectional signaling molecules in neurons. The stimuli for Nrg-1 back signaling include binding of erbB receptor dimers to the extracellular domain of Nrg-1 and neuronal depolarization. These stimuli elicit proteolytic release and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
242
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(276 citation statements)
references
References 53 publications
11
242
1
7
Order By: Relevance
“…However, our recent observations that nuclear localization of an intracellular ErbB4 epitope associates with unfavorable clinical outcome when compared to membranous ErbB4 expression (Junttila et al, 2005) suggest that enhanced ErbB4 cleavage is associated with poor survival. The functional role of soluble ErbB4 ectodomain in vivo has not been addressed but shed ErbB4 ectodomain may trap ErbB4 binding ligands (Gilmore and Riese, 2004), or even function as a ligand itself by signaling through membrane-anchored precursor isoforms of NRG-1 (Bao et al, 2003;Iivanainen et al, 2007). The mechanism leading to enhanced shedding is currently not known but may involve breast cancer-associated upregulation of expression and activity of TACE (Borrell-Pages et al, 2003;Ma¨a¨tta¨et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, our recent observations that nuclear localization of an intracellular ErbB4 epitope associates with unfavorable clinical outcome when compared to membranous ErbB4 expression (Junttila et al, 2005) suggest that enhanced ErbB4 cleavage is associated with poor survival. The functional role of soluble ErbB4 ectodomain in vivo has not been addressed but shed ErbB4 ectodomain may trap ErbB4 binding ligands (Gilmore and Riese, 2004), or even function as a ligand itself by signaling through membrane-anchored precursor isoforms of NRG-1 (Bao et al, 2003;Iivanainen et al, 2007). The mechanism leading to enhanced shedding is currently not known but may involve breast cancer-associated upregulation of expression and activity of TACE (Borrell-Pages et al, 2003;Ma¨a¨tta¨et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the 53kDa fragment detected by the antibody we used has been functionally characterized as the NRG1-ICD (Bao et al 2003;Bao et al 2004;Wang et al 1998). Only the 53kDa NRG1 protein was found to be significantly affected by diagnosis specifically in PFC cytoplasmic fractions [ANOVA: F(3,53)=5.94, p=0.001; Table 2; Figure 3].…”
Section: Nrg1 Intracellular Cleavage Domain (Nrg1-icd) Protein Levelsmentioning
confidence: 99%
“…Since full-length and cleaved NRG1 and ErbB4 can have unique functions in the cytoplasm and in the nucleus (Bao et al 2003;Bao et al 2004;Garcia et al 2000;Hahn et al 2006;Sardi et al 2006;Wang et al 1998), the levels of NRG1 and ErbB4 proteins, along with their cleavage products, may vary in mental illness according to intracellular compartment. Therefore, we examined the quantities of NRG1 and ErbB4 proteins, along with their possible cleavage products, in PFC cytoplasmic and nuclear fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that in NRG1 isoforms containing the TMc and the cytoplasmic tail (all but the β3 isoforms) a second cleavage by a γ-secretase dependent protease can occur following ligand-receptor interactions, to activate "reverse signalling" (Bao, Wolpowitz, Role, & Talmage, 2003). A cytoplasmic fragment is released, that can translocate into the nucleus and influence transcription (Bao et al, 2004).…”
Section: Nrg1 Cleavage and Consequences On Myelination Activitymentioning
confidence: 99%
“…For the contents of this figure, the authors got inspiration from different reviews and papers (Bao et al, 2003;Falls, 2003;La Marca et al, 2011;Mei & Xiong, 2008;Velanac et al, 2011).…”
mentioning
confidence: 99%